Evaluation of the Learning Environments of the UTeach Teacher Development Program for Secondary Science and Mathematics Teachers - Distin, Kimberly Anne VanHorn (Curtin University, 2016)
The UTeach teacher development program, which prepares secondary science and mathematics teachers in numerous universities across the United States, was evaluated by using a modified learning environment questionnaire in three settings. In addition to validating the questionnaire in multiple learning settings with 702 university students, the study revealed that students perceived their learning environments more positively in UTeach and field-experience classes than in STEM content classes.